Implementasi Nilai-Nilai Multikultural pada Materi Pendidikan Agama Islam dan Budi Pekerti Tinjauan Buku Teks PAI dan Budi Pekerti Kelas X SMK - Harun, Harun; Mujiono, Mus; Asiyah, Asiyah (JOEAI (Journal of Education and Instruction), 2022)
This study aims to determine whether the messages in the PAI textbook are appropriate or not. So that the messages are not conveyed in forming a good character. Therefore, this researcher wants to raise the problem, namely: How is the content of multicultural values developed in student textbooks of Islamic Religious Education and Budi Pekerti class X SMK. This research method uses a qualitative descriptive approach with the type of research that is literature (Library Research). Data collection was carried out by examining documents, namely textbooks for students of Islamic Religious Education and Budi Pekerti class X SMK. Data analysis techniques include content analysis. The results showed that: the content of multicultural values developed in the PAI and Budi Pekerti textbooks for class X SMK includes 4 values, namely 1) Tolerance Values, 2) Democracy Values, 3) Equality Values, 4) Justice Values. As for the multicultural values ​​seen from the aspects of the Qur'an in the book there is an Equivalence Value for its application, students are required to memorize the verse, the Akidah aspect has a Tolerance Value for its application in the form of believing and respecting, the Akhlaq aspect has the Value of Justice for its application by habituation, and from the aspect of Fiqh there are Values of Tolerance, Equality, and Justice in the application of this textbook for students to familiarize and apply in everyday life. Accuracy in developing multicultural values. with the components of student textbooks on Islamic religious education and good manners for class X SMK it is said to be less precise. Because the percentage of multicultural values ​​as a whole only reached 21%. Meanwhile, on the measurement scale, 21% was included in the less precise classification. Keywords: Implementation, Multicultural Values, PAI Textbooks and Moral